Isolation and molecular characterization of spermatogonia from male Sprague-Dawley rats exposed in utero and postnatally to dibutyl phthalate or acrylamide - Souza, Nathália P. [UNESP] (2019)
The increased incidence of testicular disorders in young men and the possible influence of environmental chemicals, such as dibutyl phthalate (DBP) and acrylamide (AA), requires experimental models for identifying modes of action. Most published reproductive toxicologic studies use RNA samples from the total testis to evaluate testicular gene expression; however, analyses of isolated cell types could provide a more specific tool. Among testicular germ cells, spermatogonia are critical since they represent the onset of spermatogenesis. This study aimed, (1) to establish a technique for spermatogonia isolation; (2) to apply this isolation technique to verify possible gene expression alterations (Pou5f1, Kitlg, Mki-67, Bak1 and Spry4) in prepubertal post-natal day, (PND24) and pubertal (PND45) testes after in utero and postnatal exposure to DBP or AA. The technique was efficient for isolation of a majority of spermatogonia. In utero DBP exposure led to reduced litter body weight at birth, reduced anogenital distance of male pups on PND4, and increased frequency of male nipple retention on PND14 compared to controls. DBP-exposed relative testes weights were reduced only at PND24 compared to control but they did not differ at PND45. DBP-exposed animals showed reduced expression levels of Pou5f1 and Mki67 on PND24, and reduced expression of Pou5f1 and Spry4 on PND45. AA exposure reduced expression of Pou5f1, Mki67, and Spry4 at PND45 although not significantly. Our results suggest that DBP acts by reducing cell proliferation and impairing differentiation in prepubertal and pubertal testes.